(untitled) - Page, Rick (New York, 2006)
n Make Winning a Habit, Page identifies five universal areas of sales effectiveness-Technique, Technology, Talent, Teamwork and Trust-and demonstrates how they are applied differently to the four levels of sales strategy: Individual Skills, Opportunity Management, Account Management, and Industry/Market Messaging. The result is over 20 best practices from the top sales organizations around the world. Page then shows you how to take these practices and turn them into winning results
Keywords: Sales management,Quản trị bán hàng,Quan hệ khách hàng,Selling,Customer relations